Halal Tourism in Historic Areas: Analysis of the Availability of Worship Facilities in Surabaya's Old Town - Mas'ulatur Rohmah Maulida; Hilma Yuniar Islahdiyah; Siti Khoirun Nuzulah (ASEAN Journal of Halal Study, 2026)
Based on data from the Indonesian Ministry of Religious Affairs, the Muslim population in Indonesia has reached 229.62 million people, which is the basis for the development of Muslim-friendly tourist destinations. One of the areas currently undergoing development is the old town of Surabaya, a historic area that has long been known as a center of trade and services. This study aims to analyze the adequacy of worship facilities in the Old Town of Surabaya based on DSN-MUI Fatwa No. 108/2016 and the Global Muslim Travel Index (GMTI), particularly in terms of accessibility, capacity, and fulfillment of the basic worship needs of Muslims. The research method used a mixed methods approach, combining field observations, literature studies, and questionnaires distributed to visitors. Based on the results of observations and questionnaires, worship facilities such as prayer rooms and places for wudu (ablution) are available and easily accessible to most visitors. However, there are still shortcomings in terms of accessibility for people with disabilities, the availability of worship equipment, and other supporting facilities. Respondents' assessments ranged from 3 to 4 on a scale of 5, which means that they are quite good but still need improvement.